Analysis Noe Bikomi River Water Hardness for Community Sanitation Hygiene Needs - Santiari, Made; Priyambodo, Hernur Yoga (Indonesian Journal of Chemistry and Environment, 2024)
The Noe Bikomi River water is used by the local community for daily life. The water quality of the Noe Bikomi River needs to be checked, especially the hardness parameters which can cause various consequences to guarantee the community's right to obtain good quality water. This research is quantitative descriptive research. There are 3 test sampling points where water test sampling will be carried out once in September 2023. The test sample (water) is taken from the surface and taken to the laboratory for testing. The hardness value (CaCO3) from the three points ranges from 259-277 mg/L with the high hardness level category. The hardness values at all three points still meet quality standards and are suitable for use for sanitary hygiene purposes.